KOMPONEN MAKNA KATA ‘MENCURI/MENGAMBIL’ DALAM BAHASA INDONESIA - Teguh Santosa (Balai Bahasa Sumatera Utara, 2019)
This research aims to explain the componential analyisis of meaning “mencuri” in bahasa Indonesia to contribute the Indonesian Big Dictionary (KBBI). The entry of that word in dictionary is not completed, so this research can give the rigid explanation. The word of “mencuri” can separated to three or less other word likes “mencopet”, “mengutil”, “merampok”, “membegal”and “menjambret”. All of them is the act by someone to steal the others owner. Method of this research is descriptive qualitative that the researcher tries to expalian one by one the subordinate of „mencuri‟ word. Finally, the word “mencari” have a different meaning espsecially about the meaning component.